The practicality of inclusive education in Eswatini primary schools - Phumuzani Mpofu; Nhlanhla Mkhatshwa (International Journal of Educational Management and Development Studies)
This study assessed the practical implementation of inclusive education in Eswatini primary schools and the relevant measures necessary to effectively implement inclusive education. The study was anchored on Cultural-Historical Activity Theory (CHAT) and employed participatory action research design, a qualitative methodology, and the transformative research paradigm. Purposive sampling was used in selecting the twenty-five participants. Thematic approach was used in presentation of the findings. Content analysis method was used in analysing the data. The findings of the study revealed that Eswatini primary schools are not ready to implement inclusive education. Participants lamented restrictive environment, lack of assistive technology, absence of resource centers, less qualified teachers to handle special needs children, negative attitude from teachers, parents and children, few inspectors and special needs children placed in schools without assessment reports. The study recommends setting up model inclusive schools in each cluster and placing special needs children in these schools while the government upgrades remaining schools to be inclusive. Ministries should also collaborate to make inclusivity practical in schools. Government should establish assessment structures for early identification of disability, improve teacher training, strengthen leadership, and increase inspectors.